Identifikasi Status Emosional pada Perawat yang Terlibat dalam Perawatan Covid-19 di Rumah Sakit - Liza Fauzia liza; Fitri A. Sabil; Nurul Rezki Anisa (PT.Mantaya Idea Batara, 2022)
Nurses are one of the professions that contribute to the handling of the COVID-19 outbreak. The high workload of nurses certainly must be a concern, including paying attention to the emotional status of nurses while providing COVID-19 care. The heavy workload and pressure of fear and anxiety is contagious and contagious, helplessness, and lack of experience because it is a new epidemic. The purpose of the study was to identify the emotional status of nurses involved in Covid-19 care in hospitals. This study is a quantitative study with an analytical descriptive design, the research sample was 72 respondents using a proposive sampling technique with the criteria of a minimum working period of 1 year in COVID-19 care. The questionnaire used is the DASS-42 questionnaire. The results showed that most of the respondents did not experience severe emotional status such as not being stressed, anxious, and depressed. The conclusion in this study is that nurses do not experience severe emotional status (stress, depression and anxiety) involved in treating Covid-19 in hospitals.